Characterisation of Salmonella Enteritidis Isolates from Humans, Animals and Environmental Sources - Mustakim, Maimunah (1998)
One hundred and five strains of Salmonella enteritidis isolated from five different sources including humans, food animals, avian, wild animals and environments were studied. All isolates were characterised for their biotype, plasmid profiles and resistance to antibiotics. Biotyping of the isolates subdivided them into two biotypes i.e., A and E. Subdivision of the isolates by plasmid profiling identified fifteen plasmid patterns i.e. PP0 to PP14. Plasmid pattern PP14 was the most common pattern encountered in 47 (44%) of the total isolates from various sources. Resistance to antibiotics was not uncommon with 104 (99%) of the isolates were resistant to more than one antibiotics. Subdivision by antibiotic resistance pattern exhibited ten antibiograms designated as R1 to R10. A total of 87 (82%) of the isolates fell into resistant pattern R1 which showed resistant towards erythromycin, penicillin G and triple sulpha. In conjugations studies, the ability of transferring antibiotic resistance was demonstrated in the transconjugants with the concomitant transfer of the respective plasmid and resistant to tetracycline. Sixty seven representative strains of S. enteritidis studied for restriction endonuclease digestion polymorphism by - pulsed-field gel electrophoresis (REDP-PFGE) exhibited different PFGE fragment patterns. Digestion with low-frequency-cleavage restriction endonucleases, i.e., Xbal (5'- TCTAGA-3')and Spel (5'-ACTAGT-3') produced five and three restriction patterns respectively. Interrelationships of the PFGE patterns among the isolates could be determined by the calculation of similarity index, F. The F values grouped the strains as closely related, unrelated or indistinguishable. The phage-typed strains of S. enteritidis were subdivided into one biotypes, eleven plasmid profiles, six resistance patterns and seven restriction polymorphisms. In general, characterisation by DNA-based method of plasmid profiling gave more discrimination compared to other methods. These methods also provide effective adjunct to antibiotic resistance pattern and phage typing for subdivision of S. enteritidis.